Beyond Aerobic Exercise: The Role of Resistance and Isometric Training in Hypertension Management in Older Adults — A Narrative Review - Kołkowski, Wiktor; Janiszewska, Anna; Jakubczyk, Jan; Wądołowska, Monika; Antoszewska, Magdalena; Grabowska, Maria; Gozdera, Katarzyna; Pielak, Wiktoria; Koszewski, Jakub; Oszast, Katarzyna (Quality in Sport, 2026)
Background Hypertension is a leading modifiable risk factor for cardiovascular morbidity and mortality, particularly in older adults. While aerobic exercise has traditionally been considered the foundation of non-pharmacological management, growing evidence suggests that other exercise modalities may provide comparable or even greater antihypertensive effects. Aim The aim of this review was to compare the effects of aerobic, dynamic resistance, and isometric exercise on blood pressure in older adults with hypertension, with particular emphasis on clinical effectiveness, safety, and practical usefulness. Materials and methods A narrative review of the literature was conducted using PubMed and Google Scholar. Studies published between 2021 and 2026 were included, with a focus on randomized controlled trials, systematic reviews, and meta-analyses evaluating the effects of different exercise modalities on blood pressure. Results All major exercise modalities were associated with clinically meaningful reductions in blood pressure. Aerobic exercise demonstrated consistent antihypertensive effects and remains the most established intervention. Dynamic resistance training showed comparable reductions in blood pressure and provided additional functional benefits relevant to older adults. Isometric exercise, particularly handgrip protocols, demonstrated the largest reductions in resting blood pressure in several analyses, although results were less consistent and based on more heterogeneous evidence. Conclusions Exercise remains a key component of hypertension management in older adults. While aerobic exercise continues to play a central role, resistance training should be considered an equally important therapeutic strategy. Isometric exercise appears to be a promising adjunct but requires further standardization and long-term evaluation. A multimodal and individualized approach to exercise prescription is likely to provide the greatest clinical benefit.